Low prevalence of Plasmodium malariae and Plasmodium ovale mono-infections among children in the Democratic Republic of the Congo: a population-based, cross-sectional study. (December 2016) - Doctor, Stephanie; Liu, Yunhao; Anderson, Olivia; Whitesell, Amy; Mwandagalirwa, Melchior; Muwonga, Jérémie; Keeler, Corinna; Emch, Michael; Likwela, Joris; Tshefu, Antoinette; Meshnick, Steven
Abstract Background In an effort to improve surveillance for epidemiological and clinical outcomes, rapid diagnostic tests (RDTs) have become increasingly widespread as cost-effective and field-ready methods of malaria diagnosis. However, there are concerns that using RDTs specific toPlasmodium falciparum may lead to missed detection of other malaria species such asPlasmodium malariae andPlasmodium ovale . Methods Four hundred and sixty six samples were selected from children under 5 years old in the Democratic Republic of the Congo (DRC) who took part in a Demographic and Health Survey (DHS) in 2013–14. These samples were first tested for allPlasmodium species using an 18S ribosomal RNA-targeted real-time PCR; malaria-positive samples were then tested forP. falciparum, P. malariae andP. ovale using a highly sensitive nested PCR. Results The prevalence ofP. falciparum, P. malariae andP. ovale were 46.6, 12.9 and 8.3 %, respectively. MostP. malariae andP. ovale infections were co-infected withP. falciparum —the prevalence of mono-infections of these species were only 1.0 and 0.6 %, respectively. Six out of these eight mono-infections were negative by RDT. The prevalence ofP. falciparum by the more sensitive nested PCR was higher than that found previously by real-time PCR. Conclusions Plasmodium malariae andP. ovale remain endemic at a low rate in the DRC, but the risk of missing malarial infections of these species due to falciparum-specific RDT use is low. The observed prevalence ofP. falciparum is higher with a more sensitive PCR method.